The Effect of Overconfidence and Underconfidence on Consumer Value. Issue 4 (April 2015) - Razmdoost, Kamran; Dimitriu, Radu; Macdonald, Emma K.
ABSTRACT Although the effect of knowledge miscalibration (i.e., the inaccuracy in subjective knowledge relative to objective knowledge) on consumer purchase decisions has been investigated, its effect in the usage stage of consumption is little understood. This paper examines the effect of knowledge miscalibration in terms of both overconfidence (i.e., when subjective knowledge is inflated) and underconfidence (i.e., when subjective knowledge is deflated) on the dimensions of consumer value (i.e., efficiency, excellence, play, and aesthetics). The paper makes the case that overconfidence and underconfidence should be treated separately as they trigger different consumption consequences. Several hypotheses are tested through two studies: a covariance‐based study (Study 1) and an experimental study (Study 2). In Study 1, overconfidence and underconfidence are measured, while in Study 2 they are experimentally manipulated. Findings of both studies show that underconfidence negatively influences efficiency, excellence, and aesthetics, and overconfidence negatively influences play. Also, Study 1 finds a negative effect of underconfidence on play and Study 2 finds a negative effect of overconfidence on excellence and aesthetics. Findings reveal that knowledge miscalibration negatively impacts consumers' usage experiences. This implies that in designing product or service experiences suppliers benefit from ensuring that consumers achieve a reduced level of knowledge miscalibration.